THE EFFECT OF PRICE AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT AISH SAAD ARSHIYA WORK TRAINING INSTITUTION, GOWA DISTRICT - haris, abdul (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2022)
The purpose of this study was to determine the effect of Price and Quality of Service Partially on Customer Satisfaction at the Aish Saad Arshiya Job Training Institute, Gowa Regency, and to determine the effect of Price and Quality of Service Simultaneously on Customer Satisfaction at the Aish Saad Arshiya Job Training Institute, Gowa Regency. The research method used in this study is the Quantitative Method, data collection techniques using questionnaires with Price and Service Quality variables as independent variables while Customer Satisfaction as the dependent variable; after conducting the Validity Test and Reliability Test, all data obtained from the questionnaires were declared Valid and Consistent. After testing the data using Multiple Linear Regression with 2 test instruments from the T-test, the results obtained are t count > t table (3,870 > 1.98472). Then H0 is rejected, and H1 is accepted, so the hypothesis says price (X1) affects customer satisfaction at CV. Aish Saad Arshiya is partially accepted, and t count > t table (4,192 > 1.98472) then H0 is rejected, and H1 is accepted, so the hypothesis that says there is an effect of Service Quality (X2) on customer satisfaction at CV. Aish Saad Arshiya was partially accepted. While the results of the F test, the calculated F value is 70,238 with the previously obtained F table value, which is 3.09, so it can be concluded that the calculated F value > F table or 70,238 > 3.09 and a significant level of 0.001 <0.05 then H0 is rejected, and H3 is accepted, so it can be concluded that the variable Price (X1) and Service Quality (X2) simultaneously have a significant effect on Customer Satisfaction at CV. Aish Saad Arshiya Simultaneously. The results of this study show that Price and Service Quality has a positive and significant effect on Customer Satisfaction at the Aish Saad Arshiya Job Training Institute, Gowa Regency.